Memory of the Political Secretary of the Popular Vanguard Party, San Isidro of EL GENERAL, San José, 1948 TESTIMONY OF FRANKLIN CHACON ESTRADA IN THE CIVIL WAR OF 1948 - Chacón Vargas, Lenin (2018)
Chronic political testimonial of the communist leader Franklin Chacón Estrada, in San Isidro del General. Civil War of 1948. The political Chronicle of a communist leader from the first days of the 1948 civil war, in the city of San Isidro del General of the province of San José de Costa Rica. Political memory of the preparations of what would be the military attack by foreign and national forces for the control of this city and in this way initiates the civil war. This city was defended for several days by forces loyal to the Calderonist government and by communist groups finally defeated, taking many human losses, and the military leaders of the Caribbean Legion control the population, making political prisoners to many as the author of this testimony that narrates with authenticity the days of jail and outstanding episodes, such as the one of the execution aborted by the masonic companionship and the valiant acts of the men under the command of Carlos Luis Fallas Sibaja and Commander Tijerino.